Measurement of Thermal Diffusivity, Optical Transmission and Optical Absorption Peaks of Laser Dyes R6G Doped in Poly (Methylmethacrylate) Using Photoacoustic Technique and Fibre Optics Spectrophotometer - Chan, Kok Sheng; Mat Yunus, W. Mahmood; Wan Yunus, Wan Md Zin (Universiti Putra Malaysia Press, 2003)
Using the photoacoustic (PA) spectroscopic technique, we report the thermal diffusivity measurement of the Rhodamine 6G (R6G) doped at different concentrations in solid matrix poly(methylmethacrylate) (PMMA). The value of the thermal diffusivity was found increasing with dye concentration due to the increase of optical absorption of dye molecules in the polymer matrices. A uv-visible fibre optics spectrophotometer was also used to measure the optical spectrum of the samples. The result shows that the transmission cut off in a red region (500-600) nm shifted to the higher wavelength when the dye concentration increased. The maximum transmission (83%) was observed for the PMMA sample doped with the lowest concentration of dye, i.e. 3.1 x 104 mol/ l of R6G.